PERAN KOMPUTERISASI AKUNTANSI DALAM DIGITALISASI BISNIS - Aruan, Hicca Maria Gandi Putri; Gaol, Manatap Berliana Lumban (LPPM Universitas Bina Bangsa, 2024)
This Community Service is carried out with the aim that Micro, Small and Medium Enterprises (MSMEs) realize the importance of making financial reports and know the existence of accounting applications from Bank Indonesia that can help the process of making financial reports. The method used was in the form of lectures and socialization of SAK EMKM and Computerized Accounting using the SIAPIK application. The result of this activity is that MSMEs actors in Pematangsiantar City have realized the importance of making financial reports and the existence of the SIAPIK application which can be used for free in making their business financial reports. This activity was welcomed by MSME actors and felt important to be carried out continuously